Real estate economics : a point-to-point handbook - Pirounakis, Nicholas G., 1955- (Routledge advanced texts in economics and finance ;, 2013)
"Real Estate Economics: A Point to Point Handbook introduces the main tools and concepts of real estate (RE) economics. It covers areas such as the relation between RE and the macro-economy, RE finance, investment appraisal, taxation, demand and supply, development, market dynamics and price bubbles, and price estimation. It balances housing economics with commercial property economics, and pays particular attention to the issue of property dynamics and bubbles - something very topical in the aftermath of the US house-price collapse that precipitated the global crisis of 2008. This textbook takes an international approach and introduces the student to the necessary "toolbox" of models required in order to properly understand the mechanics of real estate. It combines theory, technique, real-life cases, and practical examples, so that in the end the student is able to: - read and understand the majority of RE papers published in peer-reviewed journals - make sense of the RE market (or markets) - contribute positively to the preparation of economic analyses of RE assets and markets soon after joining any company or other organization involved in RE investing, appraisal, management, policy, or research. The book should be particularly useful to third-year students of economics who may take up RE or urban economics as an optional course, postgraduate economics students who want to specialize in RE economics, graduates of management, business administration, civil engineering, planning, and law, who are interested in RE; in addition to RE practitioners, and students reading for RE-related professional qualifications"--